Introduction to Modern Instrumentation For Hydraulics and Environmental Sciences - Guaraglia, Dardo Oscar (De Gruyter, 2014)
Natural hazards and anthropic activities threaten the human environment. The gathering of field data is needed so as to quantify the impact of such activities. To gather the necessary data researchers nowadays use a great variety of new instruments based on electronics. Yet, the working principles of this new instrumentation might not be well understood by some potential users. All operators of these new tools must gain proper insight so as to be able to judge whether the instrument is selected appropriately and functions adequately. This book attempts to demonstrate some characteristics that are not easy to understand by the uninitiated in the use of electronic instruments. The material presented in this book was prepared with the purpose of reflecting the technological changes that have occurred in environmental modern instrumentation in the last few decades. The book is intended for students of hydrology, hydraulics, oceanography, meteorology and environmental sciences. Basic concepts of electronics, special physics principles and signal processing are introduced in the first chapters in order to enable the reader to follow the topics developed in the book, without any prior knowledge of these matters. The instruments are explained in detail and several examples are introduced to show their measuring limitations. Enough mathematical fundamentals are given to allow the reader to reach a good quantitative knowledge.